THE RELATIONSHIP BETWEEN CHILDREN'S PHYSICAL FITNESS AND GENDER, AGE AND ENVIRONMENTAL FACTORS - Črtomir Matejek; Gregor Starc (ANNALES ZRS, Scientific Publishing House of ZRS Koper, 2013)
The main aim of the research was to determine how children's physical fitness development is related to age, gender, and certain environmental factors at the onset of puberty. The research was carried out on a representative sample of 897 children (47.9 % females and 52.1 % males) aged eleven and fourteen. Twelve tests were used to assess their physical fitness. Based on the duration of the physical activities, the children were divided into four categories: inactive, occasionally active, active and highly active. In the case of paternal education and maternal education, the children were classified into three categories: low, average and high. Considering their school grades in mathematics, the children were divided into three groups: less successful, successful and very successful. In the case of their place of residence, the children were divided into three groups: urban, suburban and rural. A component model of factor analysis was used to identify their basic coordinate system of physical fitness. To solve the problem of the integration of physical fitness into environmental factors, age and gender, a factorial analysis of variance was used. The results show that most of the differences in physical fitness can mainly be explained through age and gender. We can conclude that the significant factors to physical fitness development are growth, development and the maturation rate of individuals, which are predominantly hereditarily determined. Place of residence, physical activity, school grades and parental education have less influence on physical fitness development and serve only as an additional impulse to further stimulate or inhibit the physical development of children.